Changes in nectar supply: A possible cause of widespread butterfly decline - Michiel F. WALLISDEVRIES, Chris A.M. Van SWAAY, Calijn L. PLATE (Current Zoology, 2012)
Recent studies have documented declining trends of various groups of flower-visiting insects, even common butterfly species. Causes of these declines are still unclear but the loss of habitat quality across the wider countryside is thought to be a major factor. Nectar supply constitutes one of the main resources determining habitat quality. Yet, data on changes in nectar abundance are lacking. In this study, we provide the first analysis of changes in floral nectar abundance on a national scale and link these data to trends in butterfly species richness and abundance. We used transect data from the Dutch Butterfly Monitoring Scheme to compare two time periods: 1994-1995 and 2007-2008. The results show that butterfly decline can indeed be linked to a substantial decline in overall flower abundance and specific nectar plants, such as thistles. The decline is as severe in reported flower generalists as in flower specialists. We suggest that eutrophication is a main cause of the decline of nectar sources [Current Zoology 58 (3): 384-391, 2012].